Laportea decumana (Robx) Wedd. Herbal Endemic Potential from Indonesia: A Literature Review - Thalib, Abdul; Masadah, Rina; Prihartono, Prihartono; Hamid, Firdaus; Hasan, Hulan; Keliwawa, Sudin; Labulawa, Irman (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Indonesia with its tropical rainforest and its endemic flora, namely, Laportea decumana (Robx) Wedd. which is used as a traditional medicine. If we want to adopt it in complementary of nursing therapy as herbal medicine, it must be proven on an evidence-based. METHODS: The design in this study was a literature review article. Search for articles using relevant ones obtained from data based on Pubmed, Proquest, Ebsco, ScienceDirect, and Google Scholar in the span of the past 10 years (2011–2021) obtained 248 articles. RESULTS: There are seven articles that are relevant and discuss their content and use in the health. CONCLUSION: L. decumana is found in Indonesia as well as in Papua New Guinea. L. decumana (Robx) Wedd. contains alkaloids, glycosides, steroids/triterpenoids, flavonoids, tannins, and saponins which have proven their antioxidant, antibacterial, analgesic, and cytotoxic activity.